PARVULARUGOGLOBIGERINA EUGUBINA TYPE-SAMPLE AT CCESELLI (ITALY): PLANKTIC FORAMINIFERAL ASSEMBLAGE AND LOWERMOST DANIAN BIOSTRATIGRAPHIC IMPLICATIONS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
The Parvularugoglobigerina eugubina Biozone (lowermost Danian) was defined at Gubbio (Italy) to precisely define the Cretaceous/Paleogene (K/P) boundary. It was defined by the total range of Pv. eugubina, but this small morphospecies presents some taxonomic problems. The Pv. eugubina holotype and the planktic foraminiferal assemblage of the Pv. eugubina type-sample at Ceselli (Ceselli 3) were revised to precise the biostratigraphic position of this biozone. Of the 21 morphospecies identified in Ceselli 3, 14 are early Paleocene species and 7 are possible Cretaceous survivors of the K/P boundary extinction event. To clarify the lowermost Danian bizonation, it was necessary to taxonomically revise Pv. eugubina and Pv. longiapertura, which have both been identified in this sample. Following the definition of Pv. eugubina and the original definition of the nominal biozone, the base of Pv. eugubina Biozone should be placed at the first appearance datum of the eponymous species and not at the first appearance datum of Pv. longiapertura.